Design of 24-28 GHz band 5G Antenna Based on Symmetrically Located Circular Gaps - ÖZPINAR, HÜRREM; AKŞİMŞEK, HÜSEYİN SİNAN (Osman Sağdıç, 2020)
5G (fifth generation) cellular system is expected to work in a wide frequency range to meet the demand for mobile services and applications. Antennas will be addressed to the future 5G applications should pose superior characteristics, such as high gain and ultra-large bandwidth response by considering atmospheric absorption/free-space path loss on planned millimeter-wave frequency range of 5G communications. Therefore, antenna design for the future 5G applications is a challenging process. In this article we present a high-gain, broadband mm-Wave antenna based on a circular patch structure with a ground plane and resonator gaps. The designed antenna is analyzed using a widely used full-wave electromagnetic solver. The major antenna figure-of-merits including reflection coefficient, VSWR (voltage-standing wave ratio), antenna patterns in E- and H-planes, surface current distribution, antenna directivity and maximum gain, are obtained. The simulation results show that the gapped circular patch based design has the S11 response less than −10 dB in the frequency range of 21.6-28.8 GHz, which includes 24-28 GHz band of 5G cellular systems. Moreover, it is observed that the symmetrically located circular gaps on both top and bottom layers decrease the side lobe level under −10 dB value, and enhance the gain. We attribute the improvement in the antenna performance to the created current regions due to gaps hosting large vortex current distributions. With 10 mm × 13mm surface area, the proposed antenna demonstrates the peak gain of 9.44 dBi and the radiation efficiency of over 85%. High gain and compact size make this antenna suitable for coming 5G devices.
Simetrik Olarak Yerleştirilmiş Dairesel Boşluklara Dayalı 24-28 GHz bant 5G Anten Tasarımı
Keywords: 5G; Cellular Systems; Millimeter-Wave Antenna